Polycrystalline elastic moduli of a high-entropy alloy at cryogenic temperatures. (March 2015) - Haglund, A.; Koehler, M.; Catoor, D.; George, E.P.; Keppens, V.
Abstract: CrMnCoFeNi is a FCC high-entropy alloy (HEA) that exhibits strong temperature dependence of strength at low homologous temperatures in sharp contrast to pure FCC metals like Ni that show weak temperature dependence. To understand this behavior, elastic constants were determined as a function of temperature. From 300 K down to 55 K, the shear modulus ( G ) of the HEA changes by only 8%, increasing from 80 to 86 GPa. This temperature dependence is weaker than that of FCC Ni, whose G increases by 12% (81–91 GPa). Therefore, the uncharacteristic temperature-dependence of the strength of the HEA is not due to the temperature dependence of its shear modulus. Graphical abstract: